Prognostic impact of neutrophil-to-lymphocyte ratio (NLR) in patients with unresectable biliary tract cancer treated with gemcitabine, cisplatin, and durvalumab - Satoshi Mii; Hiroyuki Kato; Takeshi Takahara; Masayuki Kojima; Yutaro Kato; Zenichi Morise; Akihiko Horiguchi; Koichi Suda (World Journal of Surgical Oncology)
Abstract Background Biliary tract cancer (BTC) is a type of malignancy that is challenging to manage. Further, advanced-stage BTC has poor prognosis. Based on the recent TOPAZ-1 trial, adding durvalumab to gemcitabine and cisplatin significantly improves survival in unresectable BTC, thereby making it the new standard first-line treatment. However, real-world data are essential to validate its efficacy and safety in routine clinical settings, which often involve older patients and those with comorbidities or previous therapies. This study aimed to evaluate the outcomes of combination chemotherapy with gemcitabine, cisplatin, and durvalumab (GCD) in a real-world cohort with BTC. Methods This retrospective analysis included patients with unresectable advanced-stage BTC treated with GCD between December 2022 and April 2024 at three institutions. GCD was administered for up to eight cycles, followed by durvalumab monotherapy. Clinical data, including the characteristics of the patients, adverse events, and treatment responses, were collected. The Kaplan–Meier method and the Cox proportional hazards model were used to assess progression-free survival (PFS), overall survival (OS), and other factors affecting outcomes. Results The current study included 54 patients with a median age of 72 years. Half of the patients had recurrence post-surgery, and many of them had previously received chemotherapy. The median PFS and OS rates were 4.1 and 8.0 months, respectively. Adverse events (AEs) were frequently observed, with 42.1% of patients presenting with grade 3 or higher AEs. However, immune-related AEs were rare and mild. Dose adjustments, which are often caused by renal impairment or fatigue, were common (66.7%). Multivariate analysis revealed that older age, a lower performance status score, and a high neutrophil-to-lymphocyte ratio (NLR) were significant predictors of a shorter PFS. Further, a lower performance status score, and a high NLR were associated with a low OS. Conclusions GCD combination chemotherapy is a viable treatment option for advanced-stage BTC in a real-world setting where dose modifications can improve tolerability among elderly patients. Neutrophil-to-lymphocyte ratio can be a prognostic biomarker of OS in patients with BTC receiving immune checkpoint inhibitors. This finding highlights the potential of individualized treatment strategies. Nevertheless, further research should be performed to validate these results in larger cohorts.